A theory of type-II minimally modified gravity - De Felice, Antonio; Doll, Andreas; Mukohyama, Shinji (Journal of cosmology and astroparticle physics, 2020)
We propose a modified gravity theory that propagates only two local gravitational degrees of freedom and that does not have an Einstein frame. According to the classification in [2], this is a type-II minimally modified gravity theory. The theory is characterized by the gravitational constant GN and a function V(ϕ) of a non-dynamical auxiliary field ϕ that plays the role of dark energy. Once one fixes a homogeneous and isotropic cosmological background, the form of V(ϕ) is determined and the theory no longer possesses a free parameter or a free function, besides GN. For V′(ϕ) = 0 the theory reduces to general relativity (GR) with GN being the Newton's constant and V=const. being the cosmological constant. For V′(ϕ) ≠ 0, it is shown that gravity behaves differently from GR but that GR with GN being the Newton's constant is recovered for weak gravity at distance and time scales sufficiently shorter than the scale associated with V(ϕ). Therefore this theory provides the simplest framework of cosmology in which deviations from GR can be tested by observational data.
Gesehen am 01.02.2021